"Because I'm Blasian": Tiger Woods, Scandal, and Protecting the Blasian Brand. (24th February 2015) - Washington, Myra
Abstract : This article deconstructs the rhetoric around Tiger Woods after his extramarital affairs became public. Woods had been able to use his mixed‐race identity to market himself broadly though the scandal effectively removed any postracial claims afforded by his multiraciality. His self‐identification as mixed‐race Black and Asian to a mistress brought Blasians under scrutiny, resulting in moves to protect his commodifiability. Woods offers an interesting case study of the way Blasians, and by extension non‐White racially mixed people, are discussed in media. This article splits the coverage of Woods into 3 categories of racialization—pathological, comical, and recuperative. The multiple ways in which Blackness and Asianness were deployed offer an extended glimpse into the way Blasians trouble U.S. constructions of race.